Analisis Kriminologis dan Hukum Pidana terhadap Pembunuhan Berencana dalam Kasus Kekerasan dalam Rumah Tangga - Pratama, Arsyah Fiqi Bagas Ari; Yasarman, Yasarman (Decisio: Jurnal Ilmiah Hukum, 2024)
Domestic Violence (DV) is a serious legal and social issue that often escalates into premeditated murder, particularly when long-term abuse remains unaddressed. This study explores the criminological and legal aspects of premeditated murder in domestic violence cases, focusing on the underlying motives and challenges in law enforcement. The complexity of these cases arises from overlapping regulations between the Indonesian Penal Code (KUHP) and the Domestic Violence Law (UU PKDRT), which can impact judicial decisions. A comprehensive analysis is needed to evaluate whether existing legal frameworks effectively protect victims and deter perpetrators. This research employs a qualitative method with a normative juridical approach, utilizing primary and secondary legal sources such as legislation, court rulings, and academic literature. The collected data is analyzed through a descriptive qualitative method to systematically interpret the legal norms and practical implications. The findings indicate that economic pressures, prolonged psychological abuse, and sociocultural factors significantly contribute to premeditated murder in DV cases. Furthermore, inconsistencies in legal interpretation have led to disparities in sentencing, highlighting the need for legal harmonization. Strengthening law enforcement mechanisms, increasing judicial awareness, and enhancing victim protection services are essential to addressing this issue effectively. A multidimensional approach combining legal reforms and social interventions is necessary to mitigate domestic violence-related murders and ensure justice for victims.